2011
DOI: 10.1002/aqc.1188
|View full text |Cite
|
Sign up to set email alerts
|

Cover and edge length to area ratio of seagrass (Thalassia testudinum) meadows in coral reef lagoons (Veracruz Reef System, Southwest Gulf of México)

Abstract: ABSTRACT1. Habitat loss and habitat fragmentation are usually correlated while habitat degradation may occur independently of them. Natural and anthropogenic disturbances increase the spatial fragmentation of seagrass meadows with unknown consequences on the vegetative development achieved by seagrass.2. Cover and spatial fragmentation of Thalassia testudinum meadows in three coral reef lagoons of the Veracruz Reef System,VRS (SW Gulf of Me´xico) were quantified by analysing low-altitude images acquired by pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Competition for space from bivalves can reduce rhizome extension (Reusch and Williams, ) or density of seagrass (Booth and Heck, ) and disturbances are also associated with poor shoot‐level performance (Terrados and Ramírez‐García, ). Interestingly, eelgrass shoots may individually perform better at low density, for instance, by increasing growth or asexual reproduction (Yang, ; Ruesink et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Competition for space from bivalves can reduce rhizome extension (Reusch and Williams, ) or density of seagrass (Booth and Heck, ) and disturbances are also associated with poor shoot‐level performance (Terrados and Ramírez‐García, ). Interestingly, eelgrass shoots may individually perform better at low density, for instance, by increasing growth or asexual reproduction (Yang, ; Ruesink et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Yet, geoduck clams did have several effects within intact eelgrass meadows, which ranged from abiotic changes (increased porewater ammonium, Figure 1(C)) to modification of eelgrass density (decrease in summer density, Figure 2(A)), clonal branching (Figure 3(D)), and size (Figure 3(A)). Competition for space from bivalves can reduce rhizome extension (Reusch and Williams, 1998) or density of seagrass (Booth and Heck, 2009) and disturbances are also associated with poor shoot-level performance (Terrados and Ramírez-García, 2011). Interestingly, eelgrass shoots may individually perform better at low density, for instance, by increasing growth or asexual reproduction (Yang, 2011;Ruesink et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within seagrass beds “blowouts”—characterized by an erosional scarp, a seagrass-free blowout floor and a gently sloping seagrass-colonized leeward face—form during high wave energy events and their persistence is dependent on recurrent wave- or current-induced erosion at the scarp face ( S3 Fig ) [ 35 , 87 , 88 ]. Scarps and blowouts generally are absent in more protected, low wave-energy areas [ 35 , 87 , 89 ]. No scarps were observed at LWE sites in 1969 and 1994, but 1 or 2 scarps occurred at 3 of the 4 sites in 2016, suggesting that mean wave energy at those sites had increased sufficiently to maintain their erosion.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that these factors were less important than the degradation of adjacent healthy coral reefs in explaining localized erosion within the bay. In a comparison of seagrass beds in three coral reef lagoons of the Veracruz Reef System (SW Gulf of Mexico), Terrados and Ramírez‐García [ 89 ] observed that seagrass cover was lowest, and fragmentation and blowout number highest, by a reef that had been used as a source of building materials. They attribute this to increasing wave exposure in the lagoon through a direct anthropogenic reef-flattening effect.…”
Section: Discussionmentioning
confidence: 99%
“… 79 , have introduced the term ‘recovery length’ as a connectivity distant indication for population recovery. The perturbation size, especially edge to area ratio, is known to affect seagrass recovery time 87 , 88 and its inclusion into critical slowing down assessments will further improve our understanding and prediction to the future of seagrasses.…”
Section: Discussionmentioning
confidence: 99%